SweetGAINS Africa. Project profile. - International Potato Center (International Potato Center, 2020)
This Bill & Melinda Gates Foundation project aims to modernize Africa’s current systems for sweetpotato breeding and early generation seed production. The resulting improved varieties and their rapid dissemination and adoption will provide a strong foundation for better nutrition and diversified diets among rural and urban households across the continent.